Moral Philosophers Are Moral Experts! A Reply to David Archard - Gordon, John-Stewart (Bioethics, 2014)
In his article ‘Why Moral Philosophers Are Not and Should Not Be Moral Experts’ David Archard attempts to show that his argument from common-sense morality is more convincing than other competing arguments in the debate. I examine his main line of argumentation and eventually refute his main argument in my reply.